Risk evaluation of technology innovation in China's oil and gas industry. (1st January 2013) - Junchen, Li; Xiucheng, Dong; Höök, Mikael; Jian, Gao; Shiqun, Li
Oil and gas industries are technology intensive and appropriate risk evaluation is necessary. The Chinese oil and gas industry is in the development phase, thus risk assessments and mitigation is more important than pushing technological innovation. This paper compiles research of other experts in the field and evaluates innovation risk by using a multi-hierarchy grey method. The result shows that the technology innovation risk for China's oil and gas industry is relatively high. Finally, this paper proposes some suitable measures that may decrease risk levels.